Estudo sazonal e atividade antioxidante do óleo essencial do quimiotipo curzereno de Eugenia unifloro L. (myrtaceae) - COSTA, Jamile Silva da (2019)
The biological activity of essential oils (EOs) of several species of Eugenia (Myrtaceae) genus have been reported in the literature such as antioxidant, anti-acetylcholinesterase, antibacterial and antifungal activities. However, these activities can be affected by seasonality which promotes changes in the chemical composition. In this sense, this study aimed the evaluation seasonal of volatile compounds from Eugenia uniflora leaves, chemotype curzerene, and their antioxidant activity. The plant material was collected in Belém (PA, Brazil) during the periods of the Amazonian Winter and Summer (October/2017-September/2018). The EOs were obtained by hydrodistillation and analyzed by Gas Chromatography coupled to Mass Spectrometry (GC-MS) and the acquisition of climatological data of the collection site. The EOs yields during the dry season (1.4 ± 0.6%) did not display a statistical difference in comparison to the rainy season (1.8 ± 0.8%). The oxygenated sesquiterpene curzerene was the main compound during all periods of the annual study with amounts of 42.7% and 40.8 % in the dry and rainy period, respectively. The multivariate statistical analysis of chemical composition showed a high similarity level (46.58%) among the samples. Also, the EOs exhibited inhibition of DPPH radicals with average values of 55.0 ± 6.6%. The seasonal variability did not affect the oil yield and curzerene content of the oils, and also have a low influence on its chemical composition and antioxidant potential.